Materials for the Active Layer of Organic Photovoltaics: Ternary Solar Cell Approach - Chen, Yung-Chung; Hsu, Chih-Yu; Lin, Ryan Yeh-Yung; Ho, Kuo-Chuan; Lin, Jiann T. (ChemSusChem, 2013)
Power conversion efficiencies in excess of 7 % have been achieved with bulk heterojunction (BHJ)‐type organic solar cells using two components: p‐ and n‐doped materials. The energy level and absorption profile of the active layer can be tuned by introduction of an additional component. Careful design of the additional component is required to achieve optimal panchromatic absorption, suitable energy‐level offset, balanced electron and hole mobility, and good light‐harvesting efficiency. This article reviews the recent progress on ternary organic photovoltaic systems, including polymer/small molecule/functional fullerene, polymer/polymer/functional fullerene, small molecule/small molecule/functional fullerene, polymer/functional fullerene I/functional fullerene II, and polymer/quantum dot or metal/functional fullerene systems. All good things come in threes: Addition of a third component in bulk heterojunction solar cells (sensitizer or fullerene derivative) may increase the short‐circuit current through enhanced light harvesting and/or can increase the open‐circuit voltage through enhanced carrier mobility and modification of HOMO/LUMO energy levels. Such ternary organic solar cell systems will be reviewed in this article.